(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: The relationships of characteristics of accommodation-and-convergence pupil response with age and balance between sympathetic and parasympathetic innervation (or eutony) in healthy children and adolescents are complex and ambiguous. The results of this study were needed to select a treatment for accommodative impairments. Purpose: To investigate the efficacy of instillation of mydriatic eye drops in patients with impaired accommodation, with a consideration of both the balance of autonomic innervation and pupillography data. Materials and Methods: Seventy-one children and adolescents (age, 5 to 16 years) with impaired accommodation were treated with 1% cyclopentolate and/or 2.5% phenylephrine. The examinations included measurements of uncorrected and best-corrected visual acuity for near and distance, accommodation reserve (by the technique of Dashevsky) and autorefractometry. In addition, autonomic nervous system balance was assessed using Kerdo index (KI). Pupil responses were recorded using an OK-2 pupillographer (Ukraine). Results and Conclusion: The maximum mydriatic effect and cycloplegia were achieved within 1-2 hours after the application of 1% cyclopentolate, leading to a decrease in myopia and detection of hyperopic refractive errors, which justifies the effective use of this agent for diagnosing accommodative spasm. Using pupillography, we found that the mydriatic effect of 2.5% phenylephrine was less apparent than that of 1% cyclopentolate. Efficacy of 1% cyclopentolate and 2.5% phenylephrine was significantly higher in individuals with an increased parasympathetic tone of the ANS. We developed a combination regimen to treat accommodative impairments, with the bedtime administration of 2.5% phenylephrine (1 drop) and 1% cyclopentolate (1 drop) in both eyes (4 days on for the former only, 1 day on for the latter only, and 2 days off for both) for a month. Treatment with the combination regimen resulted in improvements in visual acuity and accommodative reserve in all patients. The regimen was well tolerated by patients, and no allergic or toxic effects were noted.